Microsystems for Pharmatechnology Manipulation of Fluids, Particles, Droplets, and Cells - Dietzel, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive, state-of-the-art review of microfluidic approaches and applications in pharmatechnology. It is appropriate for students with an interdisciplinary interest in both the pharmaceutical and engineering fields, as well as process developers and scientists in the pharmaceutical industry. The authors cover new and advanced technologies for screening, production by micro reaction technology and micro bioreactors, small-scale processing of drug formulations, and drug delivery that will meet the need for fast and effective screening methods for drugs in different formulations, as well as the production of drugs in very small volumes. Readers will find detailed chapters on the materials and techniques for fabrication of microfluidic devices, microbioreactors, microsystems for emulsification, on-chip fabrication of drug delivery systems, respiratory drug delivery and delivery through microneedles, organs-on-chip, and more.
1. A Brief Introduction to Microfluidics -- 2. Fabrication of Microfluidic Devices -- 3. Surface Functionalization of Microfluidic Devices -- 4. Microbioreactors -- 5. Microsystems for Emulsification -- 6. On-chip Fabrication of Drug Delivery Systems -- 7. Micro systems for Dispersing Nanoparticles -- 8. Particles in Microfluidic Systems: Handling, Characterization, and Applications -- 9. Respiratory Drug Delivery -- 10. Drug Delivery through Microneedles -- 11. Organ on Chip.
Keywords: Microtechnology; Microelectromechanical systems; Biomedical engineering; Biotechnology; Nanotechnology; Microsystems and MEMS; Biomedical Engineering and Bioengineering; Biotechnology; Nanotechnology